Magnetic properties and coercivity mechanism of Sm1-xPrxCo5 (x=0-0.6) nanoflakes prepared by surfactant-assisted ball milling - M. L. Xu; M. Yue; Q. Wu; Y. Q. Li; Q. M. Lu (AIP Advances, 2016)
Sm1-xPrxCo5 (x=0-0.6) nanoflakes with CaCu5 structure were successfully prepared by surfactant-assisted high-energy ball milling (SAHEBM). The crystal structure and magnetic properties of Sm1-xPrxCo5 (x=0-0.6) nanoflakes were studied by X-ray diffraction and vibrating sample magnetometer. Effects of Pr addition on the structure, magnetic properties and coercivity mechanism of Sm1-xPrxCo5 nanoflakes were systematically investigated. XRD results show that all the nanoflakes have a hexagonal CaCu5-type (Sm, Pr)1Co5 main phase and the (Sm, Pr)2Co7 impurity phase, and all of the samples exhibit a strong (00l) texture after magnetic alignment. As the Pr content increases, remanence firstly increases, then slightly reduced, while anisotropy field (HA) and Hci of decrease monotonically. Maximum energy product [(BH)max] of the flakes increases first, peaks at 24.4 MGOe with Pr content of x = 0.4, then drops again. Magnetization behavior analysis indicate that the coercivity mechanism is mainly controlled by inhomogeneous domain wall pinning, and the pinning strength weakens with the increased Pr content, suggesting the great influence of HA on the coercivity of flakes.